Capacitance enhancement by ion-laminated borophene-like layered materials - Tetsuya Kambe; Masahiro Katakura; Hinayo Taya; Hirona Nakamura; Takuya Yamashita; Masataka Yoshida; Akiyoshi Kuzume; Kaori Akagami; Ryota Imai; Jumpei Kawaguchi; Shigeyuki Masaoka; Shoichi Kubo; et al. (Nature Communications)
Abstract Atomically flat two-dimensional networks of boron are attracting attention as post-graphene materials. An introduction of cations between the boron atomic layers can exhibit unique electronic functions that are not achieved by neutral graphene or its derivatives. In the present study, we propose a synthesis strategy for ion-laminated boron layered materials in a solution phase, which enables the preparation of analogs by changing the alkali-metal species. The introduction of large cations extends the thermal range of the liquid-crystal phases because of weakened ionic interactions between borophene-like layers. An investigation of the capacitance of ion-laminated structures revealed a 105-fold or better increase in capacitance when the borophene-like materials were introduced between electrodes. That is difficult for general materials since the dielectric constant of common materials is below several thousand.